Estimation of Order Quantity and Reorder Point for an Item with RandomDemand and Delivery Time - Izar Landeta, Juan Manuel; Nájera Saldaña, José Adrián; Zárate Camacho, Lizbeth Angélica (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To apply five inventory models to obtain the order quantity and the reorder point for a product with discrete, random, independent and known demand and delivery time, considering discounts in the purchase price for acquiring larger volumes and the semi-variable order cost. MATERIAL AND METHOD: The models used were the economic order quantity (EOQ) model, applied for random demand and delivery time, the target service level (TLS) model, the normal demand distribution (ND) model, the Eppen and Martin (EM) algorithm and the Lee and Rim (LR) model. RESULTS: The differences in the results were in the reorder point value with the NS and LR models, which gave a higher value, leading to a higher inventory cost. CONCLUSIONS: All models agree on the order quantity, which is due to the unit price discount achieved by placing a larger order; three of the five models agree on the reorder point and it appears to be the correct decision in this case study.